PENYULUHAN DAN PELATIHAN PEMANFAATAN TANAMAN OBAT DI POSYANDU LANSIA HANDAYANI KELURAHAN PONCOL PEKALONGAN TIMUR - Nunung Hasanah; Andung Maheswara Rakasiwi; Siska Rusmalina (LPPM Universitas Pekalongan, 2022)
The government has formulated various elderly health care policies aimed at improving the level of health and quality of elderly health to achieve happy old age and useful in family and community life in accordance with its existence.Posyandu elderly is a center of elderly activities in the community. The benefits felt by the existence of elderly posyandu are not only felt by the elderly but also by the family and the environment in which the elderly live. Posyandu activities are a means of group learning that includes monitoring of nutritional status, blood pressure measurements, blood glucose, health counseling and other health assessment . The continuity of activities in posyandu elderly requires the activeness of posyandu members and cadres as an alarming motor. In addition to health monitoring activities, senior posyandu is also a place to increase knowledge about the elderly including prevention of diseases and alternative drugs to reduce complaints in the elderly due to decreased body function. Decreased liver function is something that occurs physiologically in the elderly so that the utilization of alternative drugs is needed. Indonesia has a variety of medicinal plants that are commonly used by the community. Examples of medicinal plants that are widely used by the community are bay leaves. Bay leaves are often used to lower blood sugar, blood pressure and uric acid because they contain antioxidants. Keywords : elderly posyandu, medicinal plants, bay leaves